Fluid restriction adherence in hemodialysis patients using the ESRD-AQ: A multicenter study - Hidayati, Wahyu; Ermawati, Eli; Firdaus, Iftinan Nida; Lestariningsih, Lestariningsih; Kristina, Tri Nur (Palembang MediRose Publisher, 2025)
Background: Patients with chronic kidney disease (CKD) undergoing hemodialysis must adhere to fluid intake restrictions to prevent fluid accumulation, which can lead to complications such as edema, hypertension, and cardiovascular events. Excess intravascular and interstitial fluid volume contributes to fluid overload, a major risk factor for morbidity and mortality in this population. Objective: To describe adherence to fluid restriction among CKD patients receiving hemodialysis and identify common barriers to adherence. Methods: This descriptive survey study was conducted from January to June 2021 at two hospitals. A total of 129 CKD patients undergoing hemodialysis were recruited through purposive sampling. Inclusion criteria were age ?18 years, receiving routine hemodialysis for at least 3 months, and ability to communicate verbally. Fluid restriction adherence was assessed using the End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ), previously validated and culturally adapted. Descriptive statistics summarized adherence patterns and patient characteristics. Results: Most participants were male, in late adulthood, had completed college, were unemployed, had been on hemodialysis for approximately 5 years, and underwent treatment twice weekly. Overall, 66% adhered to fluid restrictions, with 36.4% reporting following restrictions all the time. However, 62.8% indicated barriers to adherence, including lack of interest, inability to control fluid intake, and not understanding how to follow the restriction. Conclusion: While most CKD patients complied with fluid restrictions, a substantial proportion faced challenges that could undermine long-term outcomes. Continuous education, motivational support, and individualized counseling are essential to improve adherence. Future research should explore the association between adherence, fluid overload, and clinical outcomes.